2014
DOI: 10.1136/bjsports-2014-093494.260
|View full text |Cite
|
Sign up to set email alerts
|

Lower Limb Functional Asymmetries in Young Soccer Players: Do Differences Exist Between Different Age Groups?

Abstract: Background Functional asymmetries of the lower limbs(FA) have been recognised as a potential source of injury risk of in soccer players;moreover a difference in strength performance between the lower limbs exceeding 15% is considered an injury risk factor. Preventative strategies should be integrated into young football player training regimes. Table 1.Young soccer players: mean age 9.1±0.1 years. n.athletes>15% Total %>15% % others Hop 25 227 11,2 88,8 Triple 19 227 8,4 91,6 Side 33 227 14,5 85,5 Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…9 However, in the present research, none of the asymmetry variables were different between categories. This finding is corroborated by Kellis et al 11 who also found no differences in asymmetry between players of different ages (10 to 17 years). However, Lehance et al 28 still suggested that asymmetry decreases with age, through observation of more athletes with asymmetry in the categories Sub17 and Sub21 than in the professional categories.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…9 However, in the present research, none of the asymmetry variables were different between categories. This finding is corroborated by Kellis et al 11 who also found no differences in asymmetry between players of different ages (10 to 17 years). However, Lehance et al 28 still suggested that asymmetry decreases with age, through observation of more athletes with asymmetry in the categories Sub17 and Sub21 than in the professional categories.…”
Section: Discussionsupporting
confidence: 76%
“…When comparing soccer players of different ages, a greater percentage in the 11-year age group than in the 9-year group had >15% asymmetry, suggesting that asymmetry increases with age, 11 thereby reinforcing the hypothesis proposed and the theoretical base model. 9 However, in the present research, none of the asymmetry variables were different between categories.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Recent evidence has shown that larger asymmetries are a key factor to consider in the return to play process after injury [6], are linked to reduced neuromuscular control during hopping tasks [7], and have a detrimental effect on measures of physical performance [8,9]. Recently, Bishop et al [8] showed that greater lower-limb asymmetries in jump height were associated with reduced 5, 10, 20 m sprint and vertical jump performance in youth female soccer athletes.…”
Section: Introductionmentioning
confidence: 99%
“…When considering flexor and extensor asymmetries as a categorical variable, two classification criteria were adopted. The first classification criterion used was the 15% value based on literature 9,11,16,20 and the second criterion was to establish cutoff points based on data distribution of the study, as performed by Impellizzeri et al 13 . The upper limit value for the lateral peak torque asymmetries obtained for a sample of 64 professional soccer players was 13.80% for knee flexor muscles and 12.32% for knee extensor muscles.…”
Section: Discussionmentioning
confidence: 99%